Application of Methane Hydrate Critical State Soil Model on Multistage Triaxial Tests of Methane Hydrate-Bearing Sediment - Guo, Zehui; Wang, Zhe; Lu, Jingsheng; Li, Dongliang; Liang, Deqing; Xie, Xiaoguang; Wu, Xiaoping (International Journal of Geomechanics, 2022)
Natural methane hydrate, as a potential alternative energy source to fossil energy in the 21st century, is found in abundance in deep-water sediments and permafrost regions. During the production of methane gas from these sediments, the dissociation process may induce various changes to the geotechnical properties. Thus, it is important to study the geomechanical behavior of hydrate sediments and simulate the sediment deformation patterns. In this study, the effects of different sediment types on the mechanical properties of hydrate-bearing soils were investigated using multistage triaxial tests, and the methane hydrate critical state (MHCS) soil model was calibrated using an optimization-based technique. The results revealed that: (1) the strain-hardening phenomenon in methane hydrate-bearing sediments varies with the particle sizes of the host sediments; (2) the strengths of methane hydrate-bearing sediments are higher with the host sediments being pure sand, compared with those with clay-added sediments, and the strength is inversely proportional to the clay contents in these sediments; and (3) the multistage triaxial test data were fitted with the MHCS model, which illustrates the combined effects of the abovementioned factors on the model parameters and geomechanical behavior of methane hydrate-bearing sediments.